EFFECTIVENESS OF SIMULATION-BASED TRAINING IN THE DEVELOPMENT OF LAPAROSCOPIC SURGERY SKILLS (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
In recent years, laparoscopic surgeries have been widely used in clinical practice and have gained particular importance due to reduced rehabilitation time and a lower rate of complications in patients. However, the successful performance of laparoscopic surgical procedures requires a high level of psychomotor skills, visuomotor coordination, and spatial thinking from the surgeon [1,2]. The development of practical skills based on the traditional “mentor—trainee” model is associated with a number of challenges, including patient safety concerns, limited operative time, and the risk of errors [3]. In this regard, simulation-based training technologies are considered an integral part of modern surgical education [4,5].